Rancang Bangun Game Edukasi Drag and Drop Berbasis GDLC untuk Peningkatan Pemahaman Materi Profesi Peserta Didik Sekolah Dasar - Rezqi Ramdhani; Hani Rubiani; Sulidar Fitri (Computer Journal, 2026)
This research aims to design, develop, and test the feasibility and effectiveness of a Drag and Drop educational game (ProFuzzle) for improving first-grade elementary students' understanding of professions material. The primary challenge addressed is the scarcity of interactive media aligned with children's concrete operational cognitive development stage. The study employs a Research and Development (R&D) approach with a One-Group Pretest-Posttest design, utilizing the Game Development Life Cycle (GDLC) as the development framework. Data collection instruments include expert validation questionnaires and pretest-posttest assessments. Results show that ProFuzzle is deemed highly feasible as a learning medium, with an average expert validation score exceeding 80%. Regarding effectiveness, the game demonstrates statistically significant improvement in student understanding, evidenced by a high N-Gain score and significant t-test results. Student feedback also reflects highly positive responses. The Drag and Drop educational game developed through the GDLC method proves to be an effective, feasible, and innovative alternative medium for teaching professions material to elementary school students